The actin‐bundling protein L‐plastin supports T‐cell motility and activation. Issue 1 (10th October 2013) - Morley, Sharon Celeste
Summary: Tight regulation of actin dynamics is essential for T‐cell trafficking and activation. Recent studies in human and murine T cells reveal that T‐cell motility and full T‐cell activation require the hematopoietic‐specific, actin‐bundling protein L‐plastin (LPL). T cells lacking LPL do not form fully mature synapses and thus demonstrate reduced cytokine production and proliferation. Reduction or loss of LPL expression also reduces the velocity of T cells and impairs thymic egress and intranodal motility. Whereas dispensable for proximal T‐cell receptor and chemokine receptor signaling, LPL is critical to the later stages of synapse maturation and cellular polarization. Serine phosphorylation, calcium, and calmodulin binding regulate the bundling activity and localization of LPL following T‐cell receptor and chemokine receptor engagement. However, the interaction between these regulatory domains and resulting changes in local control of actin cytoskeletal structures has not been fully elucidated. Circumstantial evidence suggests a function for LPL in either the formation or maintenance of integrin‐associated adhesion structures. As LPL may be a target of the commonly used immunosuppressive agent dexamethasone, full elucidation of the regulation and function of LPL in T‐cell biology may illuminate new pathways for clinically useful immunotherapeutics.